1951
DOI: 10.1161/01.cir.4.6.881
|View full text |Cite
|
Sign up to set email alerts
|

Venous System of the Myocardium with Special Reference to the Conduction System

Abstract: M~yrocardial veins and sinusoids of the right atrioventricular junction of the heart were studied in serial section, and their relations to the common conduction bundle and nodal tissues were anatomically demonstrated by wax model reconstructions. It is suggested these venous channels may well explain the complete, but transient, bundle block of children observed in certain toxic diseases. On the other hand, the same sinusoids functioning as capillaries may nourish the bundle tissues in older decades, thus exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

1952
1952
1979
1979

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(3 citation statements)
references
References 2 publications
0
2
0
1
Order By: Relevance
“…Here again, the venous drainage can be considered nigh on perfect. Truex and Schwartz (1951), using reconstruction studies, showed that the veins of the atrioventricular bundle formed a sinusoid system most frequently opening into the coronary sinus and into the atrium.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here again, the venous drainage can be considered nigh on perfect. Truex and Schwartz (1951), using reconstruction studies, showed that the veins of the atrioventricular bundle formed a sinusoid system most frequently opening into the coronary sinus and into the atrium.…”
Section: Methodsmentioning
confidence: 99%
“…Truex and Schwartz (1951) also described the veins of the atrioventricular conduction system, but they regarded them as dilated sinusoids and maintained that they played an important role in facilitating the influence of toxins upon the conduction system.…”
mentioning
confidence: 99%
“…Inzwischen sind zahlreiche Untersuchungen zur Morphologie dieser sinusoidalen, intra muralen Endothelschläuche angestellt worden (2,10,20,21). Die Interpretation ihrer funk tionellen Bedeutung steht aus, und ihre Ein gliederung in das Gesamtnetz des Koronarkreislaufes ist noch nicht überzeugend gelun gen.…”
Section: Introductionunclassified